Building a suicide perception scale from a dynamic point of view, on a sample of drug addicts. A field study at the Al-Waseet Center for drug addicts - in the city of Chlef - Kachouche Saber; Yamna Smaili (Eximia, 2024)
The aim of this study was to construct a scale for suicide ideation from a dynamic perspective among drug addicts, verify its psychometric properties, and then identify differences in suicide ideation between genders. The study was conducted on a sample of 45 male and female drug addicts, 39 males and 6 females, at the Al-Wasit Center for Drug Addicts in Chlef city. After collecting the study data and conducting appropriate statistical analyses, a suicide ideation scale was developed based on Karl Menninger’s (dynamic) concept, with good validity and reliability, making it reliable for scientific studies and research. There were significant differences between genders in suicide ideation, favoring males.